2022
DOI: 10.1007/s10329-022-00973-7
|View full text |Cite
|
Sign up to set email alerts
|

Adult–adult play in captive lowland gorillas (Gorilla gorilla gorilla)

Abstract: Among African great apes, play is virtually absent between adult lowland gorillas (Gorilla gorilla gorilla). Here, we report an extremely rare case of adult–adult play observed in the lowland gorilla group housed at La Vallée de Singes (France). We recorded three playful interactions between the silverback and an adult lactating female. Given the diverse causal and functional nature of play, different factors may join in promoting this behaviour. In our group, contrary to what has been shown by previous studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(64 reference statements)
0
3
0
4
Order By: Relevance
“…In our study, we observed a reduction in agonistic behavior during the boomer ball phase compared with the control phases, as we predicted. Studies involving other species have also reported a decrease in aggressive behavior during object play behavior (e.g., Pan paniscus and Pan troglodytes [ 56 ]; Tursiops truncates [ 57 ]), while social play in adult animals can increase at times of social tension and high aggression risk (e.g., [ 58 , 59 ]). In our study, we provided one boomer ball per paca to allow access for all animals, thus minimizing potential resource disputes, although sometimes the pacas chased and tried to take the boomer ball from each other.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed a reduction in agonistic behavior during the boomer ball phase compared with the control phases, as we predicted. Studies involving other species have also reported a decrease in aggressive behavior during object play behavior (e.g., Pan paniscus and Pan troglodytes [ 56 ]; Tursiops truncates [ 57 ]), while social play in adult animals can increase at times of social tension and high aggression risk (e.g., [ 58 , 59 ]). In our study, we provided one boomer ball per paca to allow access for all animals, thus minimizing potential resource disputes, although sometimes the pacas chased and tried to take the boomer ball from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Primates -Play "give me five" -dwa osobniki bawią się twarzą w twarz, uderzając się nawzajem po spodniej powierzchni dłoni (Cordoni i współaut. 2022).…”
Section: Opis Zabawy Specyficznejunclassified
“…-Play piggy back ride -osobnik ujeżdża drugiego, siedząc na jego plecach, z nogami trzymanymi okrakiem z jego boków i wyprostowanym tułowiem (Cordoni i współaut. 2022).…”
unclassified
“…Even though play fighting is more frequent in immature individuals, in some primate species it is also retained and variably expressed in adulthood (e.g., Propithecus verreauxi-sifakas, Antonacci et al, 2010; Pan paniscus-bonobos, Palagi, 2006; Pan troglodytes-chimpanzees, Yamanashi et al, 2018; Gorilla gorilla gorilla -lowland gorillas, Cordoni et al, 2022b). For example, in bonobos play fighting is maintained at relatively high levels between adults .…”
Section: Introductionmentioning
confidence: 99%
“…Play fighting can be affected by individual (e.g., species, age, gender, and neural traits), social (e.g., affinitive and dominance relationships), and environmental (e.g., food abundance and predator presence) factors (Fagen, 1981; Pellis & Pellis, 2017). Even though play fighting is more frequent in immature individuals, in some primate species it is also retained and variably expressed in adulthood (e.g., Propithecus verreauxi —sifakas, Antonacci et al, 2010; Pan paniscus —bonobos, Palagi & Cordoni, 2012; Palagi, 2006; Pan troglodytes —chimpanzees, Yamanashi et al, 2018; Gorilla gorilla gorilla —lowland gorillas, Cordoni et al, 2022b). For example, in bonobos play fighting is maintained at relatively high levels between adults (Palagi & Cordoni, 2012).…”
Section: Introductionmentioning
confidence: 99%